Динаміка популяції Scilla siberica Haw. в урочищі “Темний ліс” (Чернігівська область) - Rak, O.O.; Penska, I.V.; Sapunova, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Aim – to investigate the dynamics of age and spatial structure of the population Scilla siberica Haw. in the tract “Dark Forest”. Material and methods. Field studies were conducted in 2013 using route-expeditionary and semi-stationary methods. Age of plants was determined by T.A. Rabotnov method with the supplements of other authors. Phytocoenotic descriptions of plant communities were carried out on the dominant basis. The age structure of the population of Scilla siberica and the determining of the population type by age structure were studied by the method proposed by T.A. Rabotnov and the A.A. Uranov school. Results. The results indicated that the population of Scilla siberica in the tract “Dark Forest” is still right-sided with a distinct maximum in generative individuals. In the population we observed the decrease in age index and increase in the average ecological density, indicating the positive dynamics of species population. Conclusion. Low ecological density of the population of Scilla siberica and its right-side range indicate the decrease in population parameters of Scilla siberica indicators on the border of areal, therefore the tract “Dark Forest” is necessary to take under protection in the status of the botanical reserve of local importance.